In search of a unified model for prediction of stock prices. - Kan, Andrew Mun Kit. (2009)
The objective of this study is to model a stock market index in Singapore as a function of major macroeconomic variables and past index values, with the aim of predicting stock market movements more accurately by combining fundamental and technical analyses. The study draws on the theoretical models and empirical results of Chen et al. (1986), Cheng et al. (1990), and Larrain (1991), a theoretical framework which integrates the arbitrage pricing theory, noise trading, and chaos theory.